Simple and Conditional Discrimination and Specific Reinforcement in Teaching Reading: An Intervention Package - Zaine, Isabela (Anal Verbal Behav, 2014)
This study evaluated an intervention package combining simple and conditional discrimination training and specific reinforcement for each stimulus class in teaching reading of simple words to individuals with intellectual disabilities. In conditional discrimination training, participants matched printed words and pictures to the recorded sounds made by the pictured objects and animals. Fourteen children and adolescents with intellectual disabilities were assigned to an experimental and a control group. The two groups’ performance did not differ in the pretest. The experimental group demonstrated equivalence class formation and read the words that participated in the equivalence classes, whereas the control group did not.